2016
DOI: 10.1093/jjco/hyw014
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and overall survival of EGFR mutation-positive non-small cell lung cancer treated with EGFR tyrosine kinase inhibitors: a retrospective analysis for 1660 Japanese patients

Abstract: BackgroundThe Japan Guidelines of Lung Cancer Therapy recommend epidermal growth factor receptor-tyrosine kinase inhibitors as a first-line therapy for advanced/recurrent non-small cell lung cancer patients with epidermal growth factor receptor mutation. Although survival periods in recent reports of epidermal growth factor receptor-tyrosine kinase inhibitor treatment have been getting longer, the reasons why are unclear. We investigated the survival, prognostic factors and real-world treatment of non-small ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 27 publications
7
57
3
2
Order By: Relevance
“…This study was a retrospective study conducted at a single institution with a small number of patients. In fact, although previous reports showed PS was the independent prognostic factor, PS was not the prognostic factor in this study. However, metastasis to multiple organs was an independent poor prognostic factor in this study, which was consistent with the previous study .…”
Section: Discussioncontrasting
confidence: 95%
“…This study was a retrospective study conducted at a single institution with a small number of patients. In fact, although previous reports showed PS was the independent prognostic factor, PS was not the prognostic factor in this study. However, metastasis to multiple organs was an independent poor prognostic factor in this study, which was consistent with the previous study .…”
Section: Discussioncontrasting
confidence: 95%
“…In this context, retrospective analysis of real-world Japanese clinical data revealed that the median OS after first-line treatment was approximately 30.8 months in patients with an EGFR mutation. 18 In contrast, the present study revealed a median OS of 32.8 months. Although it appears that our findings do not indicate inferior OS after EGFR-TKI switching, further studies with longer follow-ups are needed to evaluate this possibility.…”
Section: Discussioncontrasting
confidence: 89%
“…Third, the follow‐up period was short and 12 of the 22 patients were continuing treatment using a second EGFR‐TKI or back‐line chemotherapy at the data cut‐off point. In this context, retrospective analysis of real‐world Japanese clinical data revealed that the median OS after first‐line treatment was approximately 30.8 months in patients with an EGFR mutation . In contrast, the present study revealed a median OS of 32.8 months.…”
Section: Discussioncontrasting
confidence: 72%
“…The findings of this study provide a valuable rationale EGFR mutations [13]. In clinical practice, the majority of patients who received EGFR-TKIs have inevitable stage IV disease or postoperative recurrence.…”
Section: Discussionmentioning
confidence: 82%